A Case Study Of Digi.Com Bhd's Value-Delivery Network - Khabele, Tiisetso Slyvia (2004)
The objective of this thesis is to study DiGi's current value delivery network and improve upon it by proposing strategic partnerships that DiGi can leverage off in order to maintain its position as niche-market leader in the mobile market. By highlighting DiGi's core competencies and in identifying key parters necessary for the company's competitive edge, the proposed alliances will aid DiGi to create opportunities for successful and profitable world-class business solutions in cellular and wireless communications.